"Рокові" свята в епістолярних текстах Лесі Українки: Різдво - Богдан, С. (Культура слова, 2019)
У статті досліджено особливості функціонування в епістолярних
текстах Лесі Українки одного з найважливіших найменувань
сакрального ономастикону – геортоніма Різдво, який належить
до дванадцяти найвизначніших свят християнського календаря.
Окреслено спектр його основних функцій, встановлено типологічні
ознаки контекстів актуалізації. Проаналізовано авторське
сприйняття та оцінки цього свята й самого процесу святкування.
Виокремлено диференційні національно-культурні ознаки різдвяних
святкувань у різних країнах на основі спостережень адресантки.
З’ясовано продуктивність експлікації лексем цього словотвірного
ряду, визначено специфіку їх використання як елементів етикетних
конструкцій. The article describes the specifics of using lexeme Christmas in Lesya
Ukrainkaʼs epistolary texts. The research utilizes continuous / overall
selection techniques to reveal those specific features. Christmas belongs
to the twelve most significant holidays of the Christian calendar. The
addressee uses two basic names concerning this holiday: a rokove (annual)
festival and Christmastide. The analysis of the compiled register of all the
fixed contexts made it possible to determine four main functions of this
lexeme in its functional style: chronotopic (most productive), nominative,
ceremonial and identifying (low-productive).
Chronotope property of syntactic constructions with a lexeme Rizdvo
(Christmas) reflects the three-dimensional event space of the addresser
and its addressees, which corresponds to one of the traditions of describing
different phenomena in the national-linguistic tradition of the Ukrainians.
Each event takes place before / during or after the holiday. To convey this,
Lesya Ukrainka used the following grammatical variants: do/do samoho
Rizdva (before Christmas) and pered Rizdvom (before Christmas) – a
prospective period, ob Rizdvi and na Rizdvo (at Christmas) with a clear
predominance of the second variant – vlasne na Rizdvo (actually at
Christmas); retrospective period – vid (vid samoho) Rizdva (since the
very Christmas), z Rizdva / od Rizdva (from Christmas), po Rizdvi (after
Christmas). The customary modern Ukrainian version for post-Christmas
period «pislia Rizdva» has not been revealed in Lesya Ukrainkaʼs
epistolary texts.
The observed authorʼs evaluations of the very process of celebrating
Christmas (like other holidays) give grounds for asserting the
overwhelming negative attitude of the addresser to any holiday. Various
subjective factors are considered as the reason for it, namely poetessʼ
internal rejection of certain stereotypical traditions of celebrations (a lot of
visits, entertainments, parties).
The study elucidates the peculiarities of the Christmas greetings used in
the poetess’ letters to various addressees, which probably also determines
the linguistic mode of everyday communication of the Ukrainians, in
particular, in the family. The study has not revealed any of the typical
traditional congratulations in modern Ukrainian language – Khrystos
Narodyvsia! Khrystos rodyvsia! Khrystos Rozhdaietsia! (Christ was
born!). Alternatively, three phonetic variants of pre-Christmas greetings
are fixed – Greetings on Christmas Eve: Sviatyi Vechir! Sviatyi Vecher!
Sviatyi Vechor! (Holy Evening!).